2020
DOI: 10.1002/fsn3.1605
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative activity of oyster protein hydrolysates Maillard reaction products

Abstract: A two‐step process of enzymatic hydrolyzation followed by Maillard reaction was used to produce oyster meat hydrolysate Maillard reaction products (MRPs). The flavor of oyster meat hydrolysate MRPs was significantly improved through an optimized orthogonal experimental design. Comparisons between the antioxidative activities of oyster meat hydrolysates and their MRPs were made using lipid peroxidation inhabitation, hydroxyl radical scavenging radical activity, and radical scavenging activity of 2,2 diphenyl‐1‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Wang et al ( 47 ) found that the antioxidant property of chitosan modified by fumaric acid increased from 63 to 85% in ionic liquid solution by the DPPH free radical scavenging method. Furthermore, oyster protein hydrolysate showed superior free radical scavenging ability due to the increased phenolic and acid content after MR ( 48 ). Therefore, we concluded that MR improved the antioxidant properties of the hydrolysates, and the change in composition was essential for the increase in antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al ( 47 ) found that the antioxidant property of chitosan modified by fumaric acid increased from 63 to 85% in ionic liquid solution by the DPPH free radical scavenging method. Furthermore, oyster protein hydrolysate showed superior free radical scavenging ability due to the increased phenolic and acid content after MR ( 48 ). Therefore, we concluded that MR improved the antioxidant properties of the hydrolysates, and the change in composition was essential for the increase in antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of 1.0 ml MRPs were diluted to 100-fold with the addition of ddH 2 O. e browning degree was determined by measuring the absorbance at 420 nm using a UV-Vis spectrophotometer [13,14] (UV-2100 UNICO spectrophotometer, Jiangsu Scientific Instruments and Materials Co., LTD, Jiangsu, China).…”
Section: Determination Of Browning Degree (Bd)mentioning
confidence: 99%
“…e reducing power of the MRPs was determined according to the method previously reported [14,15] with slight modification. Samples of 1 ml MRPs (100-fold dilution) were mixed with 1.0 ml of 0.2 M sodium phosphate buffer (pH 6.6) and 1.0 ml of 1% potassium ferricyanide (K 3 Fe(CN) 6 ) in a test tube and sealed.…”
Section: Determination Of Reducing Power (Rp)mentioning
confidence: 99%
“…Te previous research proved that the favor, taste, and biological activity (antioxidant, antibacterial, etc.) of Maillard reaction products (MRPs) between protein hydrolysates/peptides and reducing sugars could be greatly improved [19][20][21][22], which is considered relatively safe and harmless in food systems. Terefore, the Maillard reaction has been deemed one of the potential alternative methods to modify the quality and function of protein hydrolysates/peptides.…”
Section: Introductionmentioning
confidence: 99%